2006
DOI: 10.5194/angeo-24-1949-2006
|View full text |Cite
|
Sign up to set email alerts
|

Reconnection and energetic particles at the edge of the exterior cusp

Abstract: Abstract. In this paper we study flux transfer events (FTE) observed at the post-noon edge of the exterior cusp region by Cluster satellites. During the outbound dayside orbit on 2 February 2003, intense bursts of energetic particles were observed in close conjuction with magnetic field FTE signatures by the RAPID instrument onboard the Cluster 4. The pitch-angle distribution of the particles showed that the enhancements consist of particles flowing antiparallel to the magnetosheath field lines away from the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Rather than drifting to the cusp (Blake et al, 1999;Delcourt and Sauvaud, 1999), Mursula (2005, 2006) suggested electrons could be released from the high latitude plasma sheet (HLPS) equatorward of the cusp to the exterior cusp via reconnection. Flux transfer event (FTE) signatures have also been observed with connections to bursts of energetic electrons (Zong et al, 2003;Asikainen and Mursula, 2006). These bursts of energetic electrons with FTE give evidence that when the geometry is appropriate, electrons can be released from the HLPS into the cusp.…”
Section: Equatorial Sourcementioning
confidence: 87%
See 1 more Smart Citation
“…Rather than drifting to the cusp (Blake et al, 1999;Delcourt and Sauvaud, 1999), Mursula (2005, 2006) suggested electrons could be released from the high latitude plasma sheet (HLPS) equatorward of the cusp to the exterior cusp via reconnection. Flux transfer event (FTE) signatures have also been observed with connections to bursts of energetic electrons (Zong et al, 2003;Asikainen and Mursula, 2006). These bursts of energetic electrons with FTE give evidence that when the geometry is appropriate, electrons can be released from the HLPS into the cusp.…”
Section: Equatorial Sourcementioning
confidence: 87%
“…3). Since very few energetic electrons were observed in the lobe, an FTE traveling from a reconnection site poleward of the cusp to the cusp would not deliver energetic electrons as is sometimes seen during time periods with reconnection equatorward of the cusp (Zong et al, 2003;Asikainen and Mursula, 2006).…”
Section: Equatorial Sourcementioning
confidence: 99%
“…Observational characteristics of this model and noted in previous studies include (1) bursts of electron flux on the equatorward edge of the cusp; (2) primarily field aligned particles flowing both into and out of the cusp; (3) a correlation between flux and solar wind speed since the HLTR is formed by radiation belt particles which correlate with solar wind speed; and (4) increased electron flux during times of southward IMF due to increased subsolar reconnection. The bursty and field aligned natures of the particles when streaming from the HLTR are noted by Asikainen and Mursula [2006] and Zong et al [2003]. The correlation between cusp electron flux and the solar wind speed as well as the IMF Bz component are shown by Asikainen and Mursula [2005].…”
Section: Discussionmentioning
confidence: 91%
“…While the FTEs observed in the low‐latitude subsolar region have consistently exhibited the characteristic bipolar signature in the magnetic normal component, it is not immediately obvious that the same is true at high latitudes. Since data from the Cluster spacecraft become available, several studies have been focused on FTEs at high latitudes to understand their structures and generation mechanisms [e.g., Lockwood et al , 2001; Wild et al , 2001, 2005; Owen et al , 2001; Zong et al , 2005; Thompson et al , 2004; Fear et al , 2005; Dunlop et al , 2005; Asikainen and Mursula , 2006]. For the high‐latitude FTEs observed in these studies, many indeed exhibit classical bipolar signatures resembling the low‐latitude ones [ Wild et al , 2001, 2005; Dunlop et al , 2005; Asikainen and Mursula , 2006] or unbalanced bipolar signatures [ Owen et al , 2001].…”
Section: Introductionmentioning
confidence: 99%